2006
DOI: 10.1007/s10461-005-9061-7
|View full text |Cite
|
Sign up to set email alerts
|

Condom Use and Its Correlates Among Female Sex Workers in Hanoi, Vietnam

Abstract: Knowledge of female sex workers' (FSW) condom use behaviors in Vietnam is importantfor predicting the epidemic and designing interventions. Four hundred FSWs in Hanoi were studied in 2002. Consistent condom use in the past month was higher with irregular clients (62%), less with regular clients (41%), and lowest with "love mates" (5%). Reasons for not using condoms were partner objection, condom unavailability, and belief of partner's disease-free status. Twenty-seven percent reported not always having a condo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
31
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 18 publications
9
31
3
Order By: Relevance
“…Our street-based FSWs showed higher baseline rates of consistent condom use than have been found previously in other street-based FSW populations in Armenia and parts of Asia and Africa, but are similar to those in Chile, Hong Kong, and China [6,[13][14][15]. In focus group discussions (Markosyan et al, unpublished), women reported previous exposure to condom use messages possibly explaining high baseline rates.…”
Section: Discussionsupporting
confidence: 78%
“…Our street-based FSWs showed higher baseline rates of consistent condom use than have been found previously in other street-based FSW populations in Armenia and parts of Asia and Africa, but are similar to those in Chile, Hong Kong, and China [6,[13][14][15]. In focus group discussions (Markosyan et al, unpublished), women reported previous exposure to condom use messages possibly explaining high baseline rates.…”
Section: Discussionsupporting
confidence: 78%
“…This study has suggested that those who reported multiple sex partners during the preceding years were less likely to use condoms consistently and more likely to engage in needle and syringe sharing behaviour. Several studies have reported sexual bridging behaviours between high risk groups and the general population (Duong et al 2008;Tran et al 2005;Tran et al 2006b). Our study suggested a high potential for HIV transmission from PLWHA to their sex partners through sexual mixing between groups.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, female sex workers use condoms less consistently with more intimate, noncommercial partners than with paying clients. [12][13][14] In addition, their reported condom use at last sex or with their most recent partner likely will not accu- …”
mentioning
confidence: 99%
“…Specifically, female sex workers use condoms less consistently with more intimate, noncommercial partners than with paying clients. [12][13][14] In addition, their reported condom use at last sex or with their most recent partner likely will not accu- used respondent-driven sampling to identify and recruit participants; this approach is a variant of snowball sampling and employs mathematical adjustments to account for the nonrandom nature of the sampling process. 19,20 The research team identified nine initial participants ("seeds"), each of whom received three recruitment coupons to recruit other sex workers.…”
mentioning
confidence: 99%